Pathophysiology of Primary Cilia: Signaling and Proteostasis Regulation - Senatore, Emanuela; Iannucci, Rosa; Chiuso, Francesco; Delle Donne, Rossella; Rinaldi, Laura; Feliciello, Antonio (Frontiers in Cell and Developmental Biology, 2022)
Primary cilia are microtubule-based, non-motile sensory organelles present in most types of growth-arrested eukaryotic cells. They are transduction hubs that receive and transmit external signals to the cells in order to control growth, differentiation and development. Mutations of genes involved in the formation, maintenance or disassembly of ciliary structures cause a wide array of developmental genetic disorders, also known as ciliopathies. The primary cilium is formed during G1 in the cell cycle and disassembles at the G2/M transition. Following the completion of the cell division, the cilium reassembles in G1. This cycle is finely regulated at multiple levels. The ubiquitin-proteasome system (UPS) and the autophagy machinery, two main protein degradative systems in cells, play a fundamental role in cilium dynamics. Evidence indicate that UPS, autophagy and signaling pathways may act in synergy to control the ciliary homeostasis. However, the mechanisms involved and the links between these regulatory systems and cilium biogenesis, dynamics and signaling are not well defined yet. Here, we discuss the reciprocal regulation of signaling pathways and proteolytic machineries in the control of the assembly and disassembly of the primary cilium, and the impact of the derangement of these regulatory networks in human ciliopathies.